MODEL PEMBELIAN PRODUK PRIVATE LABEL - Andreas Ari Sukoco (Jurnal Riset Manajemen dan Bisnis, 2014)
The growing of modern market such as minimarket, supermarket, and hypermarket has an impact on customer shopping behavior especially in development countries. Retail business offer manufactured product and private label product. Recently, private label product is growing up above manufactured product. The aim of this paper is to develop the model of buying private label product. This paper show that the buying of private label has formed some factors. This paper compile and analysis several researches that was done in India, China, Malaysia and Indonesian. The model reveals that quality, price, packaging, brand, consumer characteristics, and retail images affect the buying of private label. Keywords: private label, perception, quality, price, brand, packaging, store images,consumer characteristic, buying behavior